2022
DOI: 10.1007/s40670-021-01493-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of a Collaborative Self-Directed Learning Model in Medical Education

Abstract: Purpose One of the aims of medical education is to generate lifelong learners, leading to the identification of self-directed learning (SDL) as an essential component of medical education. While SDL is focused on an individual learner, collaboration is critically important in medicine. We developed an online course using the collaborative SDL (CSDL) framework. A goal for the course was for students to gain a better appreciation for the SDL process by exploring the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This result is consistent with the literature (Noh & Kim, 2019;Peine, Kabino & Spreckelsen, 2016;Kemp, Baxa & Cortes, 2022), which discusses the benefits of SDL in medical education as a suitable learning approach that complies with the dynamic nature of the clinical field (Noh & Kim, 2019). Benefits of SDL include motivating personal responsibility, providing independent learning and lifelong learning skills, alongside improving personal responsibility, accountability, and confidence (Noh & Kim, 2019;Kemp, Baxa & Cortes, 2022).…”
Section: Methods Of Deliverysupporting
confidence: 87%
“…This result is consistent with the literature (Noh & Kim, 2019;Peine, Kabino & Spreckelsen, 2016;Kemp, Baxa & Cortes, 2022), which discusses the benefits of SDL in medical education as a suitable learning approach that complies with the dynamic nature of the clinical field (Noh & Kim, 2019). Benefits of SDL include motivating personal responsibility, providing independent learning and lifelong learning skills, alongside improving personal responsibility, accountability, and confidence (Noh & Kim, 2019;Kemp, Baxa & Cortes, 2022).…”
Section: Methods Of Deliverysupporting
confidence: 87%
“…Future iterations could focus on emerging COVID-19 updates. On the other hand, the flexible approach to assembling this mini-series of lectures mirrored best practices in collaborative selfdirected learning, allowing participants to identify topics that addressed their knowledge gaps [27]. By making available the recordings for asynchronous access, we further supported self-directed learning, as viewers could "mix and match" topics of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent study published by Kemp and colleagues [ 24 ] found that while medical students claimed to have used and are familiar with SDL, they had not utilised aspects of SDL as defined by that study. This led the authors to speculate that students may not be able to identify components of SDL and explicit education regarding SDL may be required [ 29 ]. Other studies in the analysis commented on the potential limitations of student perceptions.…”
Section: Discussionmentioning
confidence: 99%